Oral health status and its associated factors among post-stroke inpatients: a cross-sectional study in Hungary - Júlia Moldvai; Mercédesz Orsós; Eszter Herczeg; Eszter Uhrin; Márton Kivovics; Orsolya Németh (BMC, 2022)
Abstract Background Post-stroke inpatients are at risk of poor oral health for a number of reasons. The aim of this study was to assess the oral health status of post-stroke patients and also to explore the factors that may influence it. Methods This cross-sectional study was organised at National Institute for Medical Rehabilitation in Hungary. Altogether 410 post-stroke patients were enrolled in the survey. Personal medical history and functional assessment was obtained from the final medical reports of the patients. The clinical examination and data collection were conducted according to the World Health Organization (2013) criteria. Socio-demographic background and behaviours related to oral health were assessed using a questionnaire. The dental status was explained by the number of Decayed, Missing and Filled Teeth (DMFT). The association of socio-demographic factors, stroke and functional assessment with oral health status and behaviour was evaluated. Chi-square test, Fisher's exact test, Welch test, Mann-Whitney U test, Kruskal-Wallis test, ANOVA model and correlation analysis were used to analyse our data. The level of significance was set at p < 0.05. Results Mean age of stroke patients was 59.21(Standard Deviation [SD] 14.74) years. Mean DMFT score was 20.13 (8.08), including 3.28 (4.24) decayed teeth, 15.02 (10.29) missing teeth and 1.83 (2.94) filled teeth score. Factors that influenced the oral health status were gender, age, occupational status, level of education, type and risk factors for stroke. Significant correlation was found between the Functional Independence Measure and oral health-related behaviours with patients brushing their teeth once a month showing the lowest value. Conclusion According to the results, low socio-demographic and economic status, low level of education and the Functional Independence Measure score, unemployment, the combination of risk factors for stroke and residual dysfunctions are associated with poor oral health status. The data indicate that a series of changes are needed, for special attention and care in oral health for patients who have had a stroke. Based on the findings of this research, a new model of prevention and care can be developed, with an interdisciplinary collaboration, to promote the quality of life of these individuals.